VARIASI ALIRAN TAFSIR DI ANDALUS PADA ERA KERAJAAN MUWAHHIDUN (540H/1142M – 667H/1268M): SATU TINJAUAN AWAL (Variation of Quranic Commentary in Andalus during Muwahhidun Era (540H/1142M – 667H/1268M): A Prelimenary Study) - Norasid, Muhamad Alihanafiah; Abdullah, Mustaffa (Journal of Al-Tamaddun, 2012)
This paper will discuss variations of Quranic commentary in Andalus during Muwahhidūn era (540-667H). This topic was chosen to reveal the contribution of Andalus?s exegetes highlighting the paradigm of thinking through the works they produced. Thus, the flow of this interpretation is discussed briefly by highlighting the four main commentaries, Tafsir al-Athari by Ibn `Atiyyah, tafsir bi al-Ra'y by Ibn Rushd, Tafsir al-Sufi by Ibn` Arabi, and Tafsir al-Fiqhi by Ibn al-`Arabi and al-Imam al-Qurtubi. Diversity patterns of thought manifested in the works of Quranic commentary in Andalus thus seen that the Asbania region had reached a standard that is really unique in terms of cultural accumulation of knowledge that complement each other in the era of Muwahhidūn. Tolerance and openness that exists among the Andalus?s exegetes should be emulated even implemented in the national education system for the sophisticated dynamics results in education at the national level.